Progress in research on mixing techniques for transverse injection flow fields in supersonic crossflows - Huang, Wei; Yan, Li (Journal of Zhejiang University. A. Science, 2013)
The transverse injection flow field has an important impact on the flowpath design of scramjet engines. At present a combination of the transverse injection scheme and any other flame holder has been widely employed in hypersonic propulsion systems to promote the mixing process between the fuel and the supersonic freestream; combustion efficiency has been improved thereby, as well as engine thrust. Research on mixing techniques for the transverse injection flow field is summarized from four aspects, namely the jet-to-crossflow pressure ratio, the geometric configuration of the injection port, the number of injection ports, and the injection angle. In conclusion, urgent investigations of mixing techniques of the transverse injection flow field are pro- posed, especiaUy data mining in the quantitative analytical results for transverse injection flow field, based on results from multi-objective design optimization theory.